Effect of different precursors on generation of reference spectra for structural molecular background correction by solid sampling high-resolution continuum source graphite furnace atomic absorption spectrometry: Determination of antimony in cosmetics - Barros, Ariane Isis [UNESP]; Victor de Babos, Diego [UNESP]; Ferreira, Edilene Cristina [UNESP]; Gomes Neto, José Anchieta [UNESP] (Elsevier, 2016)
Different precursors were evaluated for the generation of reference spectra and correction of the background caused by SiO molecules in the determination of Sb in facial cosmetics by high-resolution continuum source graphite furnace atomic absorption spectrometry employing direct solid sample analysis. Zeolite and mica were the most effective precursors for background correction during Sb determination using the 217.581 nm and 231.147 nm lines. Full 23 factorial design and central composite design were used to optimize the atomizer temperature program. The optimum pyrolysis and atomization temperatures were 1500 and 2100 °C, respectively. A Pd(NO3)2/Mg(NO3)2 mixture was employed as the chemical modifier, and calibration was performed at 217.581 nm with aqueous standards containing Sb in the range 0.5–2.25 ng, resulting in a correlation coefficient of 0.9995 and a slope of 0.1548 s ng−1. The sample mass was in the range 0.15–0.25 mg. The accuracy of the method was determined by analysis of Montana Soil (II) certified reference material, together with addition/recovery tests. The Sb concentration found was in agreement with the certified value, at a 95% confidence level (paired t-test). Recoveries of Sb added to the samples were in the range 82–108%. The limit of quantification was 0.9 mg kg−1 and the relative standard deviation (n=3) ranged from 0.5% to 7.1%. From thirteen analyzed samples, Sb was not detected in ten samples (blush, eye shadow and compact powder); three samples (two blush and one eye shadow) presented Sb concentration in the 9.1−14.5 mg kg−1 range.
Keywords: Antimony; Background correction; Facial cosmetics; SiO molecular spectrum